Jaminan Perlindungan Jamsostek Tenaga Kerja Tidak Tetap (Honorer) Ditinjau Dari Hukum Positif Indonesia - Putri Cahyaninghati, Ni Wayan; Kusuma, Rahmawati (Faculty of Law, University of Mataram, 2024)
This research aims to find out and discuss the guarantee of protection obtained by temporary (honorary) workers in terms of Indonesian positive law and also to find out the legal implications if this guarantee of protection is not provided. The method that the author uses in this research is normative legal research using a statutory approach and a conceptual approach. The results of this research show that guarantees of protection, especially social security, are still given to every worker, whether permanent or non-permanent, because every worker has the right to work safety obtained from agencies, companies, or state-owned or private business institutions. There are administrative sanctions against agencies, state-owned or private, companies or business institutions that do not provide or register their workers with social security.